2013
DOI: 10.6000/1929-5634.2013.02.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Exercise, and Pharmaceutical Therapies for Sarcopenic Obesity

Abstract: Sarcopenia is characterized by progressive and generalized loss of skeletal muscle mass and strength, with a risk of adverse outcomes such as physical disability, poor quality of life, and death. Sarcopenic obesity is defined as having both sarcopenia and obesity, a condition reported to be associated with a higher risk for adverse outcomes including functional disability, frailty, poor quality of life, longer hospitalization, and higher mortality rates. The definition and diagnostic criteria for sarcopenia ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…Sarcopenia refers to an age‐related reduction of muscle mass, strength, and function . The older adults experience problems with sarcopenia and high risk for obesity, causing sarcopenic obesity and vulnerability of the elderly . Older adults lose approximately 0.5% of their total skeletal muscle mass (SMM) in a day accompanied by a muscle strength reduction of 0.3–4.2% per day .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Sarcopenia refers to an age‐related reduction of muscle mass, strength, and function . The older adults experience problems with sarcopenia and high risk for obesity, causing sarcopenic obesity and vulnerability of the elderly . Older adults lose approximately 0.5% of their total skeletal muscle mass (SMM) in a day accompanied by a muscle strength reduction of 0.3–4.2% per day .…”
mentioning
confidence: 99%
“…found that RT prevents loss of muscle mass and strength, making it considerably beneficial for preventing age‐induced sarcopenia. Particularly, highly intense RT can effectively facilitate increasing the muscle strength and mass of older adults . In addition, Sarsan et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some pharmaceutical therapies (e.g., testosterone, growth hormone, ghrelin, and vitamin D) and nutritional therapies (e.g., protein and amino acid supplementation) have been studied for prevention and treatment of muscle atrophy . So far, only resistance training and some therapies (e.g., protein, amino acids with large amounts of leucine, vitamin D, nutritional compound supplementation, and formoterol) have shown any real benefits for muscles and their function . Drug treatments, including non‐steroidal selective androgen receptor modulators and anti‐myostatin / anti‐activin type II receptor antibodies, are being developed.…”
Section: Discussionmentioning
confidence: 99%